2001
DOI: 10.1084/jem.194.4.491
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Development and T Cell Responses in Mice with Mutations Affecting Tyrosines 292 or 315 of the Zap-70 Protein Tyrosine Kinase

Abstract: After stimulation of the T cell receptor (TCR), the tyrosine residues 292 and 315 in interdomain B of the protein tyrosine kinase ZAP-70 become phosphorylated and plausibly function as docking sites for Cbl and Vav1, respectively. The two latter proteins have been suggested to serve as substrates for ZAP-70 and to fine-tune its function. To address the role of these residues in T cell development and in the function of primary T cells, we have generated mice that express ZAP-70 molecules with Tyr to Phe substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 71 publications
(91 reference statements)
6
71
1
Order By: Relevance
“…Both ZAP70 Y292 and ZAP70 Y315/Syk Y352 phosphorylation patterns showed similar trends in the genotypic analysis, which was of interest because Y292 has been reported to play a role in attenuating the TCR signal and Y315 in the enhancement of ZAP70 function (26)(27)(28). The downstream signaling consequences of these two opposing regulatory effects of Y292 and Y315 is unclear, made more difficult because the phosphorylation signal obtained at Y315 also is capturing that of Syk Y352 because this anti-ZAP70 Ab cross-reacts with the Syk Y352 residue.…”
Section: Discussionmentioning
confidence: 84%
“…Both ZAP70 Y292 and ZAP70 Y315/Syk Y352 phosphorylation patterns showed similar trends in the genotypic analysis, which was of interest because Y292 has been reported to play a role in attenuating the TCR signal and Y315 in the enhancement of ZAP70 function (26)(27)(28). The downstream signaling consequences of these two opposing regulatory effects of Y292 and Y315 is unclear, made more difficult because the phosphorylation signal obtained at Y315 also is capturing that of Syk Y352 because this anti-ZAP70 Ab cross-reacts with the Syk Y352 residue.…”
Section: Discussionmentioning
confidence: 84%
“…Studies on Zap70(Y315F) in cells and mice demonstrated that Tyr 315 is important for optimal activity of Zap70 during the development of T cells in the thymus and activation of mature T cells in the lymph nodes and peripheral blood (33,54,56). Expression of Zap70(Y315F) in Syk-deficient DT40 cells impaired the function of Zap70 in BCR signaling by reducing the BCR-induced tyrosine phosphorylation of Zap70, Vav, SH2 domain-containing leukocyte protein of 76 kDa, and Shc, and attenuating the BCRinduced NF-AT-regulated responses (33).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the phosphotyrosine residues were implicated in the regulation of Zap70 catalytic activity (36, 45-47), while others, predominantly those located at the interdomain B region (see Fig. 2), were found to mediate interaction with distinct SH2-containing effector molecules (33,37,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). To test whether interdomain B-residing phosphotyrosyl residues are required for the interaction with CrkII, we used Cos-7 cells that transiently overexpress Myc-tagged WT Zap70 or Myc-tagged Zap70 ⌬265-331 proteins.…”
Section: Truncation Of the Interdomain B Region Abrogates The Abilitymentioning
confidence: 99%
“…Two of these tyrosine residues, Tyr-492 and Tyr-493 in human ZAP-70, are positioned in the activation loop of the catalytic domain, and their phosphorylation either by Lck (13,15) or by ZAP-70 itself in trans (17) contributes to the activation of ZAP-70 by stabilizing the open and extended conformation of the activation loop. Two regulatory tyrosine residues of the SH2-kinase linker, Tyr-315 and Try319, are known to become phosphorylated (16,17,19) when ZAP-70 is recruited to the TCR and have been implicated in an autoinhibitory mechanism controlling the catalytic activity of 16,17,[19][20][21][22].…”
mentioning
confidence: 99%